2018
DOI: 10.22616/erdev2018.17.n094
|View full text |Cite
|
Sign up to set email alerts
|

Vibration of foundation for rotary screw compressors installed on skid mounting

Abstract: The paper is devoted to vibration of the foundations for rotary screw compressors used for gas compression for thermo power plant installed on skid mounting. To evaluate the compressor vibration according to the industry standard VDI 3836, the user should decide whether the foundation is rigid or resilient. The foundation is rigid, if the vertical natural frequency of the foundation is at least 25 % higher than the excitation frequency. The excitation frequency, compressor running speed in Hz is normally known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Experimental modal analysis was performed using the Bump Test Module of the SKF Microlog analyzer. Literature research has shown that bump testing is sufficient for modal frequency detection alone (Bean et al, 2016; Cerpinska et al, 2018; Dekys, 2017; Dekys et al, 2018). Table 3 presents the vibration measurement parameters used for experimental modal analysis and frequency response analysis.…”
Section: Design Characterization and Resultsmentioning
confidence: 99%
“…Experimental modal analysis was performed using the Bump Test Module of the SKF Microlog analyzer. Literature research has shown that bump testing is sufficient for modal frequency detection alone (Bean et al, 2016; Cerpinska et al, 2018; Dekys, 2017; Dekys et al, 2018). Table 3 presents the vibration measurement parameters used for experimental modal analysis and frequency response analysis.…”
Section: Design Characterization and Resultsmentioning
confidence: 99%
“…Parameter dari waktu sinyal terlah dievaluasi, parameter ini adalah perpindahan, kecepatan dan akselerasi [16]. Cerpinska, et al [17], melakukan penelitian kompresor sekrup yang digunakan untuk kompresi gas untuk thermo power plan dipasang pada skid mounting, hasilnya menunjukkan bahwa getaran dalam sumbu aksial biasanya lebih tinggi untuk kompresor sekrup daripada arah radial.…”
Section: Pendahuluanunclassified
“…In actuality, a variety of mechanisms as well as potentially additional elements like vibration, errors in torque transmission, or other sporadic operational irregularities, have an impact on clearances [5] . When the vibration is too high, the compressor does not recommend excessive axial movement or a rotation speed faster than critical when there is little clearance between the rotors [6].…”
Section: Introductionmentioning
confidence: 99%